Pengembangan Data Warehouse menggunakan Metode Kimball (Studi Kasus: Ekspor & Impor Fauna dan Flora Hias Air Laut) - Tito Rhenaldi Priono; Welly Purnomo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
PT Agung Aquatic Marine or PT AAM is engaged in the field of export and import of ornamental saltwater fauna and flora, so the data from transactions and the availability of products became important in running their business operations. But those data are managed on separate divisions inside PT AAM, this could slow down the process of decision making by the executives of PT AAM. Because of that, PT AAM plans to integrate these data into a centralized source that helps in decision-making. One of the solutions to that problem is the development of a data warehouse so that the data can be integrated and makes it easier to make a decision. In the development of the data warehouse, a flow or method is used to make it easier to design and implement the data warehouse that is the Kimball or Nine-Step Kimball methodology. The data warehouse that has been developed, produces 4 dimension tables with 2 fact tables, that is fact table of ordering and purchasing. Then a requirement validation test is carried out which results in a valid status on all of the test cases. Other than that, an ETL process performance test is carried out that shows the average time of execution is Â± 24 seconds for each ETL process of fact and dimension tables. Next, an ETL process scheduling test is carried out that produces the task that runs automatically and without any problems.